Before the religious right : liberal Protestants, human rights, and the polarization of the United States - Zubovich, Gene (Intellectual history of the modern age., 2022)
In the same way that the rise of the New Right cannot be understood apart from the mobilization of evangelicals, Gene Zubovich shows that the rise of American liberalism in the twentieth century cannot be understood without a historical account of the global political mobilization of liberal Protestants.